2019
DOI: 10.1186/s12889-019-7779-9
|View full text |Cite
|
Sign up to set email alerts
|

The association of dietary patterns and adherence to WHO healthy diet with metabolic syndrome in children and adolescents: Tehran lipid and glucose study

Abstract: BackgroundThe optimal dietary pattern for reducing the extent of metabolic syndrome (MetS) has not been well established yet. The aim of this study was to evaluate dietary patterns and adherence to WHO healthy diet in children and adolescents and their associations with MetS.MethodsSubjects of this cohort study were selected from among children and adolescents of the Tehran Lipid and Glucose Study participants, aged 6–18 years (n = 424). Dietary measurements were collected using a valid and reliable food frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 43 publications
4
20
0
2
Order By: Relevance
“…The higher intakes of total protein, total fat, SFA, TFA, and cholesterol showed by the highest MetSSS may have been due to the high consumption of total, red, and processed meat and other oils and fats different from olive oil, and it is consistent with previous results in which the quality and the amount of FA intake were associated with risk of MetS [48]. Previous findings showed a decrease in cardiovascular risk on reductions of SFA intake [49], like our results on lower SFA intake in lower severity MetSSS participants.…”
Section: Dietary Characteristicssupporting
confidence: 91%
“…The higher intakes of total protein, total fat, SFA, TFA, and cholesterol showed by the highest MetSSS may have been due to the high consumption of total, red, and processed meat and other oils and fats different from olive oil, and it is consistent with previous results in which the quality and the amount of FA intake were associated with risk of MetS [48]. Previous findings showed a decrease in cardiovascular risk on reductions of SFA intake [49], like our results on lower SFA intake in lower severity MetSSS participants.…”
Section: Dietary Characteristicssupporting
confidence: 91%
“…Previous studies have revealed that diet-related behaviors can influence individuals' health. For example, dietrelated behaviors are associated with mortality and morbidity of non-communicable diseases [1], risk of certain diseases (cardiovascular disease [9,10], metabolic syndrome [11][12][13], and cancer [9,14]), and all-cause mortality [9]. Knowledge and attitudes indirectly affect individuals' health status by promoting behavior change [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A large sample size, one of the strengths of this study, revealed the associations of added or free sugars intake with Glu, SBP, and metabolic syndrome score. However the ORs for metabolic syndrome or most of other risks were not significant even with a large sample size, which is comparable to those of other studies on Asian adolescents [24,25]. Other than BMI, we used metabolic variables that might be a rare complicated confounder of energy intake.…”
Section: Discussionmentioning
confidence: 65%
“…There have been few studies investigating the association between intake of sugars or SSBs and cardiovascular risks among Asian adolescents. Studies on adolescents from Korea [ 21 ], China [ 22 ], Japan, and Cambodia [ 23 ] examined the association of sugars intake with body fatness, while studies from Korea [ 24 ] and Iran [ 25 ] examined the association with metabolic risk factors, and showed no significant associations. Therefore, the aim of this study was to examine the association between added or free sugars intake and metabolic biomarkers other than adiposity in Japanese adolescents and to evaluate high intake of sugars to identify adolescents with cardiometabolic risks.…”
Section: Introductionmentioning
confidence: 99%